Transcriptomics and metabolomics reveal effect of arbuscular mycorrhizal fungi on growth and development of apple plants - Jing, Shan; Li, Yuchao; Zhu, Lingcheng; Su, Jing; Yang, Tianyi; Liu, Bowen; Ma, Baiquan; Ma, Fengwang; Li, Mingjun; Zhang, Manrang (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi (AMF) and plants form a symbiotic relationship that promotes plant growth and development. However, the regulatory mechanisms through which AMF promote plant growth and development are largely unexplored. In this study, the apple rootstock M26 was assessed physiologically, transcriptionally and metabolically when grown with and without AMF inoculation. AMF significantly promoted the number of lateral root (LR) increase and shoot elongation. Root transcriptomic and metabolic data showed that AMF promoted lateral root development mainly by affecting glucose metabolism, fatty acid metabolism, and hormone metabolism. Shoot transcriptomic and metabolic data showed that AMF promoted shoot elongation mainly by affecting hormone metabolism and the expression of genes associated with cell morphogenesis. To investigate whether shoot elongation is caused by root development, we analyzed the root/shoot dry weight ratio. There was a correlation between shoot growth and root development, but analysis of root and shoot metabolites showed that the regulation of AMF on plant shoot metabolites is independent of root growth. Our study bridged the gap in the field of growth and development related to AMF.